Total Syntheses and Preliminary Biological Evaluation of Brominated Fascaplysin and Reticulatine Alkaloids and Their Analogues - Zhidkov, Maxim E. (Mar Drugs, 2019)
A simple approach toward the synthesis of the marine sponge derived pigment fascaplysin was used to obtain the marine alkaloids 3-bromofascaplysin and 3,10-dibromofascaplysin. These compounds were used for first syntheses of the alkaloids 14-bromoreticulatate and 14-bromoreticulatine. Preliminary bioassays showed that 14-bromoreticulatine has a selective antibiotic (to Pseudomonas aeruginosa) activity and reveals cytotoxicity toward human melanoma, colon, and prostate cancer cells. 3,10-Dibromofascaplysin was able to target metabolic activity of the prostate cancer cells, without disrupting cell membrane’s integrity and had a wide therapeutic window amongst the fascaplysin alkaloids.